Studi Literatur: Efektifitas Terapi Garam sebagai Upaya Pengobatan Granuloma Umbilikal - Nur Rohmah Prihatanti; Noor Adha Aprilea (Malang Journal of Midwifery (MAJORY), 2022)
Umbilical granuloma is granular tissue that appears in the center of the umbilical cord after the baby's umbilical cord is detached. Umbilical granuloma is reported to occur in 1 in 500 newborns. Umbilical granuloma is closely associated with delayed formation of the umbilical cord and the presence of an inflammatory process or mild infection in the umbilical cord. A literature study was conducted to determine the effectiveness of salt therapy in the treatment of umbilical granuloma. The criteria for the articles reviewed are articles with a range of 2018-2022 and using the Google Scholar database. The keywords used are "Salt" and "Umbilical Granuloma" or "Garam" and "Granuloma Umbilikal". Based on the five articles that have been reviewed, all articles discuss the effectiveness of salt therapy to treat granuloma although there are some differences in the application process. Treatment of umbilical granuloma with salt is very effective with a cure rate of 96%, safe, uncomplicated, inexpensive, easily available, and can be done by anyone.